Experimental and Numerical Investigation of the Seismic Performance of RC Moment Resisting Frames - Esfandiari, Javad; Roudsari, Mehrzad Tahmouli; Esfandiari, Soheil (Periodica polytechnica. Civil engineering. Bauingenieurwesen, 2024)
The rehabilitation of concrete structures has been a subject of extensive investigation, exploring various facets. One such avenue involves the incorporation of fiber additives into concrete materials. In parallel, the construction of reinforced concrete structures inevitably encounters construction errors, necessitating constant efforts from researchers to devise solutions for mitigating their impact. In the context of this research, a series of experiments was conducted involving the construction and testing of five reinforced concrete moment-resisting frames. The initial sample served as the control, while two additional samples were integrated with polypropylene and metal fibers. The subsequent two samples deliberately introduced a manufacturing error through the application of air-entraining admixture materials at the beam-to-column connection. This deliberate error aimed to assess the influence of additive fibers on frames affected by manufacturing errors. Several critical parameters were subjected to evaluation, including ultimate strength, stiffness, ductility, energy dissipation capacity, and strength reduction factor. The results of these assessments demonstrated that the utilization of additive fibers contributes to an enhanced overall performance of the frames, as inferred from the aforementioned seismic parameters. Furthermore, it was established that the incorporation of these additive fibers substantially alleviates the impact of manufacturing errors on moment-resisting reinforced concrete frames. Although a significant reduction in energy dissipation capacity was observed in samples with manufacturing errors, the other seismic parameters remained relatively unaffected. Subsequently, numerical models were generated in ABAQUS software to validate the experimental findings, and their outcomes were compared with the results derived from the physical experiments.